CCL2 Overexpression in the Brain Promotes Glial Activation and Accelerates Tau Pathology in a Mouse Model of Tauopathy - Joly-Amado, Aurelie; Hunter, Jordan; Quadri, Zainuddin; Zamudio, Frank; Rocha-Rangel, Patricia V.; Chan, Deanna; Kesarwani, Anisha; Nash, Kevin; Lee, Daniel C.; Morgan, Dave; Gordon, Marcia N.; Selenica, Maj-Linda B. (Frontiers in Immunology, 2020)
Innate immune activation is a major contributor to Alzheimer’s Disease (AD) pathophysiology, although the mechanisms involved are poorly understood. Chemokine C-C motif ligand (CCL) 2 is produced by neurons and glial cells and is upregulated in the AD brain. Transgene expression of CCL2 in mouse models of amyloidosis produces microglia-induced amyloid beta oligomerization, a strong indication of the role of these activation pathways in the amyloidogenic processes of AD. We have previously shown that CCL2 polarizes microglia in wild type mice. However, how CCL2 signaling contributes to tau pathogenesis remains unknown. To address this question, CCL2 was delivered via recombinant adeno-associated virus serotype 9 into both cortex and hippocampus of a mouse model with tau pathology (rTg4510). We report that CCL2 overexpression aggravated tau pathology in rTg4510 as shown by the increase in Gallyas stained neurofibrillary tangles as well as phosphorylated tau-positive inclusions. In addition, biochemical analysis showed a reduction in the levels of detergent-soluble tau species followed by increase in the insoluble fraction, indicating a shift towards larger tau aggregates. Indeed, increased levels of high molecular weight species of phosphorylated tau were found in the mice injected with CCL2. We also report that worsening of tau pathology following CCL2 overexpression was accompanied by a distinct inflammatory response. We report an increase in leukocyte common antigen (CD45) and Cluster of differentiation 68 (CD68) expression in the brain of rTg4510 mice without altering the expression levels of a cell-surface protein Transmembrane Protein 119 (Tmem119) and ionized calcium-binding adaptor molecule 1 (Iba-1) in resident microglia. Furthermore, the analysis of cytokines in brain extract showed a significant increase in interleukin (IL)-6 and CCL3, while CCL5 levels were decreased in CCL2 mice. No changes were observed in IL-1α, IL-1β, TNF-α. IL-4, Vascular endothelial growth factor-VEGF, IL-13 and CCL11. Taken together our data report for the first time that overexpression of CCL2 promotes the increase of pathogenic tau species and is associated with glial neuroinflammatory changes that are deleterious. We propose that these events may contribute to the pathogenesis of Alzheimer’s disease and other tauopathies.